2013
DOI: 10.1371/journal.pone.0060147
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Randomized, Double Blind, Placebo Controlled Rectal Safety and Acceptability Study of Tenofovir 1% Gel (MTN-007)

Abstract: ObjectiveRectal microbicides are needed to reduce the risk of HIV acquisition associated with unprotected receptive anal intercourse. The MTN-007 study was designed to assess the safety (general and mucosal), adherence, and acceptability of a new reduced glycerin formulation of tenofovir 1% gel.MethodsParticipants were randomized 1∶1:1∶1 to receive the reduced glycerin formulation of tenofovir 1% gel, a hydroxyethyl cellulose placebo gel, a 2% nonoxynol-9 gel, or no treatment. Each gel was administered as a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 25 publications
3
84
2
Order By: Relevance
“…A small increase in ATP6 expression was observed in response to both the HEC and TDF gels. This observation contrasts with data obtained from a recent phase 1 clinical study of the rectal safety of a 1% TFV gel (31). Using a microarray approach, the investigators found that 505 genes were downregulated in response to seven doses of a 1% TFV gel, including ATP6 and other genes associated with mitochondrial function (F. Hladik, L. Flemming, J, McElrath, and I. McGowan, presented at the Microbicide Trials Network Annual Meeting, Bethesda, MD, 10 to 13 February 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…A small increase in ATP6 expression was observed in response to both the HEC and TDF gels. This observation contrasts with data obtained from a recent phase 1 clinical study of the rectal safety of a 1% TFV gel (31). Using a microarray approach, the investigators found that 505 genes were downregulated in response to seven doses of a 1% TFV gel, including ATP6 and other genes associated with mitochondrial function (F. Hladik, L. Flemming, J, McElrath, and I. McGowan, presented at the Microbicide Trials Network Annual Meeting, Bethesda, MD, 10 to 13 February 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…variety of chemokines and cytokines, including TNF-a and IL1b. 38 Combined with reports from MTN-007, 39 these findings merit ongoing attention in future trials. Although the participants demonstrated high adherence by the measures used, it was quite clear that only a minority of TFV gel recipients liked the product, providing an additional, user-based rationale to develop/test rectal specific formulations.…”
Section: Discussionmentioning
confidence: 87%
“…While these new products are directed at reducing the incidence of HIV among men who have sex with men (MSM), it has also been acknowledged that heterosexual anal intercourse may be underreported due to social taboos and other factors (27)(28)(29). This issue has shifted the paradigm of microbicide development toward a new generation of dual-compartment microbicides that are safe for both vaginal and rectal use (30,31). Hence, in this study, we used models of rectal and vaginal mucosal transmission to evaluate the potential of topically applied nAbs.…”
Section: Discussionmentioning
confidence: 99%